A sulfur-containing hetero-octulene: synthesis, host–guest properties, and transistor applications. Issue 69 (29th July 2020) - Yang, Longfei; Zhang, Ning; Han, Yi; Zou, Ya; Qiao, Yanjun; Chang, Dongdong; Zhao, Yan; Lu, Xuefeng; Wu, Jishan; Liu, Yunqi
Abstract : A heterocycloarene derivative (S-Octulene ) possessing two sulfur atoms was conveniently synthesized through Bi(OTf)3 -catalyzed cyclization from a macrocyclic tetramethoxyethenylated precursor. Abstract : A heterocycloarene derivative (S-Octulene ) possessing two sulfur atoms was conveniently synthesized through Bi(OTf)3 -catalyzed cyclization from a macrocyclic tetramethoxyethenylated precursor. The physical properties of S-Octulene and its supramolecular host–guest interaction with C60 and C70 were investigated by fluorescence titration and 1 H NMR. The solution-processed organic field-effect transistor (OFET) measurements demonstrated that S-Octulene behaved as a p-type semiconductor with a hole mobility exceeding 0.01 cm 2 V −1 s −1 . Our findings pave a new path to design novel heterocycloarenes for the development of host–guest chemistry and organic semiconductors.